Pengaruh Islamic Corporate Governance (ICG) dan Islamic Corporate Social Responsibility (ICSR) terhadap Kinerja Perbankan Syariah di Indonesia (Studi Empiris Pada Bank Umum Syariah (BUS) Periode 2020-2024) - Annisa Tulmardiah; Septria Susanti (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
The development of Islamic banking in Indonesia requires the strengthening of governance and social responsibility practices to improve institutional performance. However, the implementation of Islamic Corporate Governance (ICG) and Islamic Corporate Social Responsibility (ICSR) in Islamic Commercial Banks remains relatively limited, and previous studies have produced inconsistent findings regarding their impact on banking performance. This study aims to examine the influence of ICG and ICSR on the performance of Islamic banking in Indonesia. The research employs a quantitative approach using secondary data obtained from Islamic Commercial Banks during the observation period. Data were analyzed using descriptive statistics, classical assumption tests, and multiple linear regression analysis to evaluate the relationship between the variables. The findings show that Islamic Corporate Governance has a positive and significant effect on the performance of Islamic banking in Indonesia. In contrast, Islamic Corporate Social Responsibility does not show a significant effect on banking performance. Simultaneously, ICG and ICSR contribute to the variation in Islamic banking performance, although the magnitude of the influence is relatively limited. These results suggest that strengthening governance practices plays a more prominent role in improving Islamic banking performance, while the implementation of social responsibility requires further optimization to create a stronger impact.